DIRECTIONS OF ENSURING NATIONAL CURRENCY STABILITY AND THE MAIN ASPECTS OF THE DEVELOPMENT OF FOREIGN EXCHANGE RATE IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A national currency is a legal tender issued by a country’s central bank or monetary authority. It is typically the predominant medium of exchange for purchasing goods and services. In Uzbekistan, the uzbek soum (UZS) is the primary form of currency, backed by the full faith and credit of the government and the National Reserve. In Uzbekistan the Central Bank has the right to oblige commercial banks to keep the minimum mandatory reserves in special reserves. Stabilization of such reserves is determined by the type of bank’s liabilities, deposit and lifetime. This mechanism is mainly used to coordinate the volume of liquid assets of commercial banks.